First Evidence of the Presence of the Causative Agent of Caseous Lymphadenitis—Corynebacterium pseudotuberculosis in Dairy Products Produced from the Milk of Small Ruminants - Denisa Langova; Iva Slana; Jana Okunkova; Monika Moravkova; Martina Florianova; Jirina Markova (Pathogens, 2022)
This study focused on the detection and quantification of selected bacteria and on the presence of enterotoxin genes in milk and dairy products from sheep and goat farms in the Czech Republic using quantitative real-time PCR (qPCR) and multiplex PCR (PCR). The presence of Corynebacterium pseudotuberculosis (CP), Mycobacterium avium subsp. paratuberculosis (MAP), Listeria monocytogenes, Staphylococcus aureus, S. aureus enterotoxin genes and methicillin-resistant Staphylococcus aureus (MRSA) was determined in 18 milk samples, 28 fresh cheeses, 20 ripened cheeses and 14 yoghurts. The serological status of the herds in relation to CP and MAP was taken into account. The most frequently detected bacterium was S. aureus (48.8%), and subsequent PCR revealed 11 MRSA positive samples. The S. aureus enterotoxin genes seg, sei and sec were detected in two goat cheeses. Cheese samples showed a statistically higher risk of SA and MRSA occurrence. CP (8.8%) and MAP (13.8%) were detected by qPCR on two different seropositive farms. Cultivation of qPCR positive CP samples on agar plates supplemented with potassium tellurite showed the presence of viable bacterium. The results obtained confirmed the necessity of monitoring the infectious status of dairy animals and rapid diagnosis of bacterial pathogens in milk and dairy products.